Interactive video for learning Mathematics element of measurement in elementary school - Setyo Ajie Wibowo; Made Duananda Kartika Degeng; Henry Praherdhiono (Himpunan Pengembang Kurikulum Indonesia (HIPKIN), 2024)
Mathematics learning needs to be delivered using learning media to make it easier for students to receive information and increase student motivation. Creating interesting learning media is the solution to make it easier for students to receive the material. This research aims to produce an interactive video for learning elementary school measurement math that can motivate students to learn. The method used in this research is development research with the Lee and Owen development model. The development model consists of 5 stages: analysis, design, development, implementation, and evaluation. The validation results showed positive results that are very feasible to use. The trial in the actual class has been proven by the student's response to using the developed media, which is seen in ease, attractiveness, and motivation. Developing interactive videos can be considered accessible, exciting, and motivating for elementary school students to learn. AbstrakPembelajaran Matematika perlu disampaikan dengan menggunakan media pembelajaran sehingga memudahkan peserta didik dalam menerima penyampaian informasi serta meningkatkan motivasi peserta didik. Pembuatan media pembelajaran yang menarik menjadi solusi yang ditawarkan untuk mempermudah peserta didik dalam menerima materi. Penelitian ini bertujuan untuk menghasilkan interaktive video untuk pembelajaran matematika elemen pengukuran sekolah dasar yang dapat memotivasi peserta didik untuk belajar. Metode yang digunakan dalam penelitian ini adalah penelitian pengembangan dengan model pengembangan Lee and Owen. Model pengembangan terdiri dari 5 tahapan analisis, desain, pengembangan, penerapan, dan evaluasi. Hasil validasi menunjukkan hasil positif sehingga media sangat layak untuk digunakan. Uji coba pada kelas sebenarnya telah dibuktikan dengan respons peserta didik terhadap penggunaan media yang dikembangkan dilihat dari aspek kemudahan, kemenarikan, dan motivasi. Pengembangan interaktif video dapat disimpulkan mudah, menarik, dan memotivasi belajar peserta didik sekolah dasar.Kata Kunci: Elemen pengukuran; Matematika; sekolah dasar; video; video interaktif